Wpływ odejścia od normalności rozkładu na poprawność zastosowania miar ryzyka systematycznego - Homa, Magdalena; Mościbrodzka, Monika (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
The aim of this paper is to examine the distribution of rates of return of the chosen Investment Funds (the representatives of groups with different investment strategies) and to examine the influence of the departure from normality on the correctness of employment of the classic and downside beta index (semi-beta). The empirical tests are based on the analysis of linear regression on weekly sets of rates of return of the Investment Funds listed on the Warsaw Stock Exchange (GPW) which is the basis of the calculated classic and downside beta index (semi-beta). The results of empirical tests indicate that regardless the investment strategy of an Investment Fund there is basis to reject the hypothesis of normal distribution of rates of return in the long period, which means above all the necessity of employment of the downside systematic risk measures which point out that the real systematic risk is higher than it would result from the classic beta. The presented results are a recommendation for the investment fund managers concerning the systematic risk evaluation method.
Keywords: systematic risk; beta index; semi-beta